STRENGTHENING THE VALUE OF INTEGRITY IN CORPORATE GOVERNANCE TO REALISE STRONG, BALANCED AND SUSTAINABLE GLOBAL ECONOMIC GROWTH TOWARDS GOLDEN INDONESIA IN 2045 - sunarto sunarto; Muhammad Ricza Irhamni (Universitas Wahid Hasyim Semarang, 2024)
ABSTRACTThis research aims to apply the value of integrity in corporate governance to achieve strong, balanced, and sustainable global economic growth towards a golden Indonesia in 2045. This research design is ex post facto, namely from something that is done afterwards. The analysis technique used is descriptive to see events in the form of rare or unusual phenomena that may not be anticipated and can provide valuable insights and contribute to understanding for management in actualising good corporate governance. The results of the study concluded that the steps that need to be implemented by management in good corporate governance by actualising the value of integrity include: humble, honest, patient, sincere, trustworthy, fighting spirit in working and offering the best work. This research has practical implications for the management of business entities or companies in increasing economic productivity, creating stability and anticipating crises that will be faced by the global community towards the Golden Indonesia in 2045.